Balancing Food Security, Environmental Health, and Political Agendas: A Case Study of Food Estate in Kalimantan Tengah - Rovik, Anwar; Khaidir, Said; Ishak, Muhammad (BKM Public Health and Community Medicine, 2024)
Purpose: To discuss the current condition of food estate in Kalimantan Tengah, the environmental and social costs, and how to balance the competing interests. Results: Food security is a global concern. The food estates in Central Kalimantan represent a strategic initiative of the Indonesian government aimed at bolstering national food security through the establishment of extensive, integrated agricultural zones. However, they also come with significant environmental and social costs. Large-scale deforestation and habitat disruption associated with food estates can force wildlife closer to human populations and livestock. Excessive use of pesticides and fertilizers in food estates can contaminate water sources, impacting aquatic life and harming human health. The relationship is complex and often fraught with tension. Balancing these competing interests requires a multi-pronged approach. The policy should be applied in the open-participatory concept, where all parties involved are involved in formulating, implementing, and evaluating the policy. Thus, the policy becomes the fruit of collective thinking, and there is a sense of ownership of each party to the policy. Not only from the implementation side but also from the evaluation process. In food estates, the use of resources is tied to the emergence of clientelism practices, where social, economic, and political ties form a very hierarchical network in the implementation of food estates. The lack of alignment and sustainable planning in implementing the food estate has also led to failure in maintaining the desired power through the program. Conclusion: Sustainable public policies, community engagement, and a shift towards environmentally friendly agricultural practices are crucial for ensuring food security for the future without compromising public and environmental health.